"We Are More Than Crime Fighters": Social Media Images of Police Departments. (December 2018) - Hu, Xiaochen; Rodgers, Kourtnie; Lovrich, Nicholas P.
Currently, about 96% of U.S. police departments have adopted social media, nearly 94% of which have implemented Facebook . Unfortunately, researchers have not paid much attention to police use of social media. The study serving as the basis for this article entails a careful analysis of 14 of the most popular police Facebook pages and analyzes posts during a 1-year period. The study documents 5 major themes and 24 noteworthy subthemes, and then applies a two-step cluster analysis to identify four principal types of police Facebook social images: crime fighter, traditional cop, public relations facilitator, and mixer. The well-established diffusion of innovations literature is employed to provide justification for the timeliness of the study, and the work of Rogers and subsequent scholars building upon it serves as the principal theoretical framework for this study. Public policy implications for policing are discussed, along with appropriate directions for further research.